Fabrication and characterization of composite biodegradable films from chitosan and corn silk - Mohd Faizan, Jamaluddin (2009)
Composite biodegradable film made from chitosan has been most potential type of packaging especially in food packaging. It has caught many reserches and scientist attention to fully utilize its function as it posses not great physical properties to produce films, it is also environmental friendly and also has mycotoxin properties. The most suitable additives has not yet to be discovered but organic fibers is the best candidate as it has organic fibers to enhance the film even there was few synthethic materials such as polylactic acid. By using corn silk and starch, as an fiber is the concern of the study in therms of theoritically enhancing the physical and chemical properties of the composite biodegradable film.Corn silk also has great properties in physical where it may consist of Zein a corn protein which is good in physical. It also contain some of chemical compound that is good to fight the mycotoxins. The film preparation process consist of hydrolyzation of corn silk fibers which was done at a temperature range of 80°C before to be mixed with chitosan based solution. The solution was poured on a glass plate and left at ambient temperature until it has become dry. The film was then peeled off the glass plate after the drying is complete. Based on the study, the fibers from corn silk do gives an extra physical properties for the chitosan-base composite film. The melting point has change to a more better value in order to sustain more heat during packaging before it gradually melts compared to chitosan alone. After the fiber being added with starch, the composite film able to give higher melting point Furthermore,the mechanical and thermal strength increase but only by small value. This is due to the effect of miscibility of solution before casting it to be a film. Results obtain from FTIR, TGA, DSC and AFM proved that by using corn silk as an additive, the composite film is experimentally enhanced in terms of physical properties. From the study, it can be concluded that the fibers from corn silk fiber has a great potential for being fiber to support the matrix base composite film but there must be further research on how to mix the fiber well with the starch.